Implementation of the Contextual Teaching and Learning Model in the Al-Liqo Al-Usbuiyyah Program: Case Study in Higher Education in Indonesia - Salma Nazhimah; Faqihulhikam Mohammad (Journal of Arabic Language Learning and Teaching)
University students generally study Arabic with the aim of understanding Islamic study sources such as the Al-Qur'an and hadith, specifically as a means of verbal and written communication. However, from the results of initial observations, researchers found that the interest and motivation of students at one of the State Islamic Religious Universities (PTKIN) in Indonesia in mastering Arabic still needed to be higher. In an effort to overcome this problem, the PTKIN management created a program called al-liqo al-usbuiyyah using the Contextual Teaching and Learning (CTL) learning model. Therefore, this research aims to explore the efforts made by PTKIN management to foster student interest and motivation in mastering Arabic. A qualitative descriptive research method with a case study approach was used in this research. The results of this research show that the al-liqo al-usbuiyyah program using the Contextual Teaching and Learning (CTL) learning model runs well and is proven to be able to increase student interest and motivation in mastering Arabic. This research also describes several obstacles experienced in implementing this program, such as limited time, busy and varied lecture schedules, students' psychological conditions, and heterogeneous initial understanding of members.